Contrasting sapling bark allocation of five southeastern USA hardwood tree species in a fire prone ecosystem. Issue 7 (17th July 2015) - Hammond, Darcy H.; Varner, J. Morgan; Kush, John S.; Fan, Zhaofei
Abstract : Fire affects numerous aspects of plant growth and anatomy, particularly in those species adapted to persist in fire‐prone environments. A key aspect of tree survival is rapid accumulation of protective bark within fire return intervals. We compared bark accumulation in five co‐occurring hardwood species within a longleaf pine ( Pinus palustris ) ecosystem in the mountains of northeastern Alabama, USA. Sampled species included blackjack oak ( Quercus marilandica ), sand hickory ( Carya pallida ), common persimmon ( Diospyros virginiana ), rock chestnut oak ( Quercus montana ), and red maple ( Acer rubrum ). Using bark thickness and inside bark diameter measurements taken at 20‐cm intervals along the main stem of saplings (average age 4–5 years) we found that, while average wood diameter did not differ across species, significant differences occurred in the ratio of bark to wood. Bark comprised over half (bark:wood = 0.55) of the basal diameter of blackjack oak, which was 3×, 4×, and 6× greater than the bark:wood ratio of sand hickory and rock chestnut oak, common persimmon, and red maple, respectively. Bark taper revealed that while other species allocated similarly to bark along the length of their stem, blackjack oak allocated much more at its base (in the flaming zone) and relatively less as height increased. Red maple, a commonly cited invader during fire‐free intervals, invested the least in bark thickness and, with rock chestnut oak, had an average height and height:diameter ratio significantly greater than blackjack oak and all other species, respectively. These results confirm the adaptive importance of bark thickness to enhancing species survival in frequent fire regimes.